The on-line low temperature nuclear orientation facility NICOLE. (8th March 2017) - Ohtsubo, T; Roccia, S; Stone, N J; Stone, J R; Gaulard, C; Köster, U; Nikolov, J; Simpson, G S; Veskovic, M
Abstract: We review major experiments and results obtained by the on-line low temperature nuclear orientation method at the NICOLE facility at ISOLDE, CERN since the year 2000 and highlight their general physical impact. This versatile facility, providing a large degree of controlled nuclear polarization, was used for a long-standing study of magnetic moments at shell closures in the region Z  = 28, N  = 28–50 but also for dedicated studies in the deformed region around A  ∼ 180. Another physics program was conducted to test symmetry in the weak sector and constrain weak coupling beyond V–A . Those two programs were supported by careful measurements of the involved solid state physics parameters to attain the full sensitivity of the technique and provide interesting interdisciplinary results. Future plans for this facility include the challenging idea of measuring the beta–gamma–neutron angular distributions from polarized beta delayed neutron emitters, further test of fundamental symmetries and obtaining nuclear structure data used in medical applications. The facility will also continue to contribute to both the nuclear structure and fundamental symmetry test programs.